Polymerization of ɛ-caprolactone using Ru(II) Catalysts: mechanistic insights - Mendes, Paulo J. (2012)
Ring-opening polymerization of cyclic esters is an important field in polymerization chemistry due to the biocompatibility and biodegradability of the obtained materials. Even if the literature concerning the ROP of lactones is vast, there is not detailed research for Group 8 transition metal based catalysts or initiators. It was only in 2006 that was reported the first example regarding the use of ruthenium derivatives in ROP of lactones. In this contribution we present the results of the polymerization of ε-caprolactone by [Ru(η5-C5H5)(η6-substituted arene)][PF6] complexes in the presence of isopropyl alcohol. By in situ NMR techniques it was found that this polymerization proceeds via an activated monomer mechanism. A DFT study of the polymerization initiation step will also be presented in order to corroborate this mechanism.